Investigating the Suitability of Cement Stabilized Murram Soil as Mortar for Construction. - Siende, Isaac (Kabale University, 2023)
Masonry mortar is a homogenous mixture comprising of fine aggregates, binding material and water. The increase in the cost and demand of sand for construction is becoming a problem and making the construction more expensive in some parts of the country. Therefore, the replacement of sand-based mortars with soil-based mortars will be economical in the construction. This research addresses on an experimental study to understand the suitability of cement stabilized murram soil of G3 as mortar for construction. Critical properties of mortar have been studied i.e., Workability and Plasticity, Flexural and Compressive Strength, the Bond strength, the Initial and Final setting time of the mortars. The mortar with 0%, 15%, 20%, 25%,50%, 60%, and 75% replacement of sand in murram soil and without varying the percentage of cement was conducted. Their compressive and flexural strength obtained. The compressive strength at the age of 28 days lied within the range of 9.73MPa to 16.42MPa which is acceptable as per the IS code specification, the minimum strength requirement of mortar to be 3 MPa. The initial and final setting time lied in the range of 120 minutes and 150 minutes and the final setting time lied in the range of 270 minutes and 300 minutes for cement and murram mortars respectively. The recommended range of mortar to be used for construction is 30 minutes minimum and 600 minutes maximum for initial and final setting time respectively. The workability of the murram mortar was 82% and the plasticity index of the murram soil was 25%, which lied within the recommended range. The conclusions of the investigation of murram soil shows that the use of cement stabilized murram mortar can be applied in construction as far as the investigated parameters are concerned.